Electromanometry in biliary surgery: new acquisitions on the dynemia of the sphincter of Oddi. Oddi’s registration unit. Synergy. Oddi - morphine duodenum. Preliminary note - Cosco Montaldo, Homero (Cirugía del Uruguay, 2020)
Presented at session 8th June 1962